Development of Standard Operating Protocols for the Optimization of Cannabis-Based Formulations for Medical Purposes - Baratta, Francesca; Simiele, Marco; Pignata, Irene; Ravetto Enri, Lorenzo; Torta, Riccardo; De Luca, Anna; Collino, Massimo; D’Avolio, Antonio; Brusa, Paola (Frontiers in Pharmacology, 2019)
Under current legalisation in Italy, Cannabis for medical purposes may be administered orally in the form of decoction or Cannabis oil extract. The scientific literature reports a number of preparation methods, mainly for oils, but no studies are available which compare thoroughly, from a technological viewpoint, the Cannabis-based formulations currently administered to patients. With this in mind, this research work aimed to carry out specific formulation studies in order to design standard operating procedures for preparation and optimisation of Cannabis-based galenic formulations. Both decoctions and oils were prepared under different operating conditions in order to identify the most efficient process for the production of formulations with a high concentration of decarboxylated THC and CBD. Regarding Cannabis oil, a new procedure has been developed which allows significantly higher recovery rates for THC and CBD compared to those for water-based extraction methods (decoction) as well as those for the oil-based methods currently in use. Moreover, based on the results, it is possible to affirm that the prescription of Cannabis-based decoctions should not be the recommended first-choice solution for therapy: considering the low concentration of THC and CBD and, consequently, the high volume of decoction that the patient would have to ingest.